Novel RPL13 Variants and Variable Clinical Expressivity in a Human Ribosomopathy With Spondyloepimetaphyseal Dysplasia. (13th October 2020) - Costantini, Alice; Alm, Jessica J; Tonelli, Francesca; Valta, Helena; Huber, Céline; Tran, Anh N; Daponte, Valentina; Kirova, Nadi; Kwon, Yong‐Uk; Bae, Jung Yun; Chung, Woo Yeong; Tan, Shengjiang; et al.
ABSTRACT: Spondyloepimetaphyseal dysplasias (SEMDs) are a heterogeneous group of disorders with variable growth failure and skeletal impairments affecting the spine and long bone epiphyses and metaphyses. Here we report on four unrelated families with SEMD in which we identified two monoallelic missense variants and one monoallelic splice site variant in RPL13, encoding the ribosomal protein eL13. In two out of four families, we observed autosomal dominant inheritance with incomplete penetrance and variable clinical expressivity; the phenotypes of the mutation‐positive subjects ranged from normal height with or without hip dysplasia to severe SEMD with severe short stature and marked skeletal dysplasia. In vitro studies on patient‐derived dermal fibroblasts harboring RPL13 missense mutations demonstrated normal eL13 expression, with proper subcellular localization but reduced colocalization with eL28 ( p < 0.001). Cellular functional defects in fibroblasts from mutation‐positive subjects indicated a significant increase in the ratio of 60S subunits to 80S ribosomes ( p = 0.007) and attenuated global translation ( p = 0.017). In line with the human phenotype, our rpl13 mutant zebrafish model, generated by CRISPR‐Cas9 editing, showed cartilage deformities at embryonic and juvenile stages. These findings extend the genetic spectrum of RPL13 mutations causing this novel human ribosomopathy with variable skeletal features. Our study underscores for the first time incomplete penetrance and broad phenotypic variability in SEMD‐RPL13 type and confirms impaired ribosomal function. Furthermore, the newly generated rpl13 mutant zebrafish model corroborates the role of eL13 in skeletogenesis. © 2020 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR)..